2018
DOI: 10.1002/ece3.4295
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid‐specific δ15N trophic enrichment factors in fish fed with formulated diets varying in protein quantity and quality

Abstract: Compound‐specific isotope analysis (CSIA) of amino acids (AAs) in consumer tissues is a developing technique with wide‐ranging applications for identifying nitrogen (N) sources and estimating animal trophic level. Controlled experiments are essential for determining which dietary conditions influence variability in N stable isotopes (δ15N) trophic enrichment factors in bulk tissue (TEFbulk) and AAs (TEFAA). To date, however, studies have not independently evaluated the effect of protein quantity and quality (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 92 publications
(247 reference statements)
4
45
1
Order By: Relevance
“…In addition, consumers that excrete nitrogen as ammonia rather than as urea or uric acid have higher Δ 15 NC-D values [74], possibly because the relatively greater toxicity of ammonia requires this molecule to be excreted rapidly, which can cause substantial fractionation [37,75]. Values of Δ 15 NC-D can also vary among tissues [76,77] with the highest values occurring in tissues with very active metabolic processing of AA, such as liver [73]. Unique physiological processes can also affect Δ 15 NC-D. A recent study of captive leopard sharks (Triakis semifasciata) found surprisingly low Δ 15 NC-D values for trophic AA [72], likely related to the ability of elasmobranchs to retain and recycle urea nitrogen into newly-synthesized AA [31,76].…”
Section: Csia Applications To Datementioning
confidence: 99%
“…In addition, consumers that excrete nitrogen as ammonia rather than as urea or uric acid have higher Δ 15 NC-D values [74], possibly because the relatively greater toxicity of ammonia requires this molecule to be excreted rapidly, which can cause substantial fractionation [37,75]. Values of Δ 15 NC-D can also vary among tissues [76,77] with the highest values occurring in tissues with very active metabolic processing of AA, such as liver [73]. Unique physiological processes can also affect Δ 15 NC-D. A recent study of captive leopard sharks (Triakis semifasciata) found surprisingly low Δ 15 NC-D values for trophic AA [72], likely related to the ability of elasmobranchs to retain and recycle urea nitrogen into newly-synthesized AA [31,76].…”
Section: Csia Applications To Datementioning
confidence: 99%
“…Although assumed to change minimally between diet and consumer, source AAs such as Phe may also vary in trophic enrichment (Nuche‐Pascual et al. ) and may even be depleted in 15 N compared to the diet (Steffan et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent review by McMahon and McCarthy (2016) showed that the trophic fractionation of Glu and Phe is not as consistent as initially assumed. Fractionation of Glu may vary depending on diet quality (Hoen et al 2014, Blanke et al 2017, Nuche-Pascual et al 2018 and mode of N excretion (Germain et al 2013). Although assumed to change minimally between diet and consumer, source AAs such as Phe may also vary in trophic enrichment (Nuche-Pascual et al 2018) and may even be depleted in 15 N compared to the diet (Steffan et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach assumes that analytical and methodological errors are similar for CSIA-AA and bulk SIA. However, Elemental Analyzer -Isotope Ratio Mass Spectrometry (EA-IRMS) used in bulk SIA typically operates with an analytical precision (0.1 -0.2 ‰) that is substantially higher than what is reported in CSIA-AA studies (0.4 -1.0 ‰; Bradley et al 2016;Broek and McCarthy 2014;Broek et al 2013;Chikaraishi et al 2015;Hetherington et al 2017;Nuche-Pascual et al 2018;Ogawa et al 2013;Ruiz-Cooley et al 2017;Vane et al 2018;Vokhshoori et al 2019). This lower precision is the result of a lengthy and time-consuming analytical process inherent to the Gas Chromatography-Combustion-IRMS (GC-C-IRMS) used for almost all CSIA-AA work.…”
Section: Introductionmentioning
confidence: 98%